Fuzzy Logic with PI Controller and Multivariable Filter for Harmonic Reduction Based Hybrid Active Power Filter (The International Journal of Engineering & Information Technology (IJEIT), 2025)
In this paper, a Fuzzy Logic used with Proportional Integral (PI) controller to regulate the DC bus voltage of Hybrid Power Filter (HPF) in order to improve power quality of the three-phase distribution system. The electricals and electronics equipment generate a large quantity of harmonics currents which effects several problems in the supply system. The principal goal of this study is to improve the efficiency of HPF, suppress harmonics currents and consequently reduce Total Harmonic Distortion (THD) under 5%. The suggested control mechanism is d-q theory based on Multivariable Filter (MF) and Fuzzy Logic for extracting reference currents. The efficiency of combined fuzzy logic and PI controller is evaluated by the simulation study using Matlab/Simulink software and the obtained results are presented.